2020
DOI: 10.5194/acp-20-5513-2020
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of hydrogen peroxide in gas-liquid and gas-aerosol phases

Abstract: Abstract. Hydrogen peroxide (H2O2) is a vital oxidant in the atmosphere and plays critical roles in the oxidation chemistry of both liquid and aerosol phases. The partitioning of H2O2 between the gas and liquid phases, or the aerosol phase, could affect its abundance in these condensed phases and eventually the formation of secondary components. However, the partitioning processes of H2O2 in gas-liquid and gas-aerosol phases are still unclear, especially in the ambient atmosphere. In this study, field observat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 65 publications
1
32
0
Order By: Relevance
“…39 We consider this difference to Atmospheric Implications. The decomposition of α-HHs contributes to the formation of H 2 O 2 and multifunctionalized species in the aerosol phase, 3,4,10 which play an important role in modulating many atmospheric processes. Our results show that the stability of α-HHs in aqueous media is markedly increased as the temperature is decreased, implying that the lifetimes of α-HHs in aerosols are affected by local temperatures under different environmental conditions (e.g., altitude, day/night, season, and weather).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…39 We consider this difference to Atmospheric Implications. The decomposition of α-HHs contributes to the formation of H 2 O 2 and multifunctionalized species in the aerosol phase, 3,4,10 which play an important role in modulating many atmospheric processes. Our results show that the stability of α-HHs in aqueous media is markedly increased as the temperature is decreased, implying that the lifetimes of α-HHs in aerosols are affected by local temperatures under different environmental conditions (e.g., altitude, day/night, season, and weather).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Simultaneous measurements of particle-bound and gas phase H 2 O 2 concentrations suggest that it partitions much more efficiently to the particle phase than predicted on its physical Henry's law constant (K H,H2O2 = 1.02•10 5 M atm -1 ). Despite large uncertainties in such measurements and of related parameters such as the aerosol water content, various studies revealed that the partitioning of H 2 O 2 between the gas and the aerosol aqueous phases may be more appropriately described with an effective Henry's law constant of K H,eff,H2O2 ≤ 2.7•10 8 M atm -1 (Hasson and Paulson, 2003;Xuan et al, 2020). The observation by Hasson and Paulson (2003) of higher H 2 O 2 concentrations in coarse mode particles than in fine mode particles might point to a sizedependent chemical particle composition with higher iron content in coarse particles that often contain dust.…”
Section: Relative Difference In Phase Transfer Rates ∆R Pt [Ros]mentioning
confidence: 99%
“…Previous studies on the possibility of mass transfer of H2O2 from rain water to the surrounding air indicate a possible release of hydrogen peroxide to the atmosphere (Hua et al, 2008;Huang and Chen, 2010;Xuan et al, 2020). Raindrops are affected by the temperature gradient between the earth's surface and the cloud base.…”
Section: The Fate Of Hydrogen Peroxide Below Cloudsmentioning
confidence: 99%
“…The negative dependence of hydrogen peroxide solubility on temperature derived from the Henry's law constant means that an impact on the aqueous-gas phase equilibrium can be assumed. Moreover, the mass transfer coefficient is dependent on the surface-to-volume ratio of the rain drops and is diminished for large rain drops due to a smaller contact surface between the liquid and gas phase (Xuan et al 2020). The size of the raindrops can be derived from the rain intensity, as shown by Kumar, 1985).…”
Section: The Fate Of Hydrogen Peroxide Below Cloudsmentioning
confidence: 99%